Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1021/je101086r
|View full text |Cite
|
Sign up to set email alerts
|

Vapor−Liquid Equilibrium Data of the Carbon Dioxide + Ethyl Butyrate and Carbon Dioxide + Propylene Carbonate Systems at Pressures from (1.00 to 13.00) MPa and Temperatures from (313.0 to 373.0) K

Abstract: High-pressure vaporÀliquid equilibrium data for the binary systems of ethyl butyrate (EB) þ carbon dioxide and propylene carbonate (PC) þ carbon dioxide were measured. The experimental pressure range was from (1.00 to 13.00) MPa and the temperature range from (313.0 to 373.0) K. Experimental results were correlated with the PengÀRobinson equation of state with the two-parameter van der Waals mixing rule. At the same time, the Henry's coefficient and solution enthalpy and solution entropy of CO 2 during dissolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 11 publications
4
21
0
Order By: Relevance
“…These reported CO 2 solubility data can be also compared with those reported in the literature by our group previously [18] as well as by others [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. From table 4 and figure 4, it can be seen that the values of CO 2 solubility in PC are in excellent agreement with published data by Blanchard et al [18].…”
Section: Experimental Datasupporting
confidence: 87%
See 4 more Smart Citations
“…These reported CO 2 solubility data can be also compared with those reported in the literature by our group previously [18] as well as by others [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. From table 4 and figure 4, it can be seen that the values of CO 2 solubility in PC are in excellent agreement with published data by Blanchard et al [18].…”
Section: Experimental Datasupporting
confidence: 87%
“…Figure 3 represents the CO 2 solubility data, expressed in mole fraction of CO 2 (a) as well as in Henry's Law constants (b) at the atmospheric pressure, in the selected pure solvents as a function of temperature. It can be observed that the CO 2 is more soluble in linear solvents than in cyclic carbonates, as already described in the literature by our group [18] and others [23,33].…”
Section: Experimental Datasupporting
confidence: 80%
See 3 more Smart Citations